Spectroscopy of Cu- and Ag-doped single crystal and glassy lithium tetraborate: luminescence, optical absorption and ESR study - Ignatovych, M.; Holovey, V; Vidoczy, T.; Baranyai, P.; Kelemen, A.; Laguta, V.; Chuiko, O. (Functional Materials, 2005)
Photoluminescence (PL), optical absorption (ОА) and ESR spectra have been studied to characterize Cu- and Ag-doped single crystal and glassy Li₂B₄О₇ (LTB). The attribution of LTB:Cu glass PL as one arising from the sets of Cu⁺ ions with slightly different local environments is proposed. The ОА spectra of Cu-doped single crystal and glass are different in the UV and VIS ranges. The ОА and PL features of LTB:Ag single crystal and glassy are different from each other. Исследованы спектры фотолюминесценции (ФЛ), оптического поглощения (ОП) и ЭПР для характеристики монокристаллов и стекла тетрабората лития (ТБЛ), легированных Cu и Ag. Предложена интерпретация ФЛ стекла ТБЛ:Cu, как обусловленной набором Cu⁺ ионов в несколько отличных локальных окружениях. Спектры ОП монокристаллов и стекла отличаются как в УФ, так и в видимой части спектра. Показано, что спектры ОП и ФЛ монокристаллов и стекла ТБЛ:Ag также различны. Дослiджено спектри фотолюмiнесценцiї (ФЛ), оптичного поглинання (ОП) та ЕПР для характеристики монокристалiчного та склоподiбного тетраборату лiтiю (ТБЛ), легованого Cu та Ag. 3апропоновано iнтерпретацiю ФЛ скла ТБЛ:Cu як такої, що зумовлена набором Cu⁺ iонiв у дещо вiдмiнних локальних оточеннях. Спектри ОП монокристалiв та скла ТБЛ:Cu вiдрiзняються один вiд одного як в УФ, так i y видимiй дiлянках спектра. Спектри ОП монокристалiв та скла ТБЛ:Ag також вiдрiзняються один вiд одного.